Manajemen Madrasah dalam Mempertahankan Kualitas Kerja Guru pada Massa Pandemi Covid 19 di Madrasah Aliyah Swasta Al Fuad - Alamsyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study describes madrasa management in maintaining the quality of teacher work during the COVID-19 pandemic at Al Fuad private madrasah aliyah. The purpose of this research is to educate the readers and evaluate madrasa principals and teachers so that they continue to innovate to improve the quality of work. This type of research is a qualitative research that seeks to describe social phenomena that are developing in the present mass. The data collection techniques he did were observation and unstructured interviews and then the data was analyzed objectively and then described scientifically by following the procedures for writing scientific papers. training on learning planning and learning models by utilizing social media technology. Second, the madrasah principal continues to supervise the teachers in the form of monitoring the online learning process and the list of student assessments according to student competence. Third, the head of the madrasah urges the teachers not to conduct gathering activities in the madrasa environment so that it does not become a cluster of transmission of Covid 19. Fourth, the head of the madrasah evaluates the work of teachers every month by implementing a strict health protocol. Fifth, the madrasa head determines the teacher's attendance schedule as much as 50% per day and limits working time in the madrasa according to the instructions from the Covid 19 task force and then adjusts the subject matter according to the curriculum set by the government.